Pie goes on forever, so you round it to 3.14.
3.14*2= 6.28
Hope that helped!
Answer:
Step-by-step explanation:
3 consecutive integers....
1st integer = x
2nd integer = x + 1
3rd integer = x + 2
the product of 1st and 3rd is 5 greater then 5 times the 2nd...
x(x+2) = 5(x + 1) + 5
x^2 + 2x = 5x + 5 + 5
x^2 + 2x = 5x + 10
x^2 + 2x - 5x - 10 = 0
x^2 - 3x - 10 = 0
(x - 5)(x + 2) = 0
x - 5 = 0 x + 2 = 0
x = 5 x = -2
so it will be : 5,6,and 7 or -2,-1, and 0
Answer:
True, True, False
Step-by-step explanation:
Answer:
The correct answer is first option
u² - 11u + 24 = 0
When u = (x² - 1)
Step-by-step explanation:
It is given that,
(x² - 1)² - (x² - 1) + 24 = 0
<u>To find the correct answer</u>
Substitute u = x² - 1
The equation becomes,
u² - 11u + 24 = 0 Where u = (x² - 1)
Therefore the correct answer is first option
u² - 11u + 24 = 0
When u = (x² - 1)